Morbidity profile in a rural community-based rehabilitation programme in Butembo, North Kivu Province, Congo - Prosperine V. Masika; Prosper M. Lutala (AOSIS, 2011)
Background: Medicine in low socio-economic countries is primarily disease-oriented; prevention and rehabilitative care are secondary concerns. Hence, curative care erodes the few resources allocated to health. Despite the well-documented benefits of communityrehabilitation in the management of chronic conditions, little is known about common conditions present in the community in Butembo. Objectives: The objective of this study was to determine the conditions encountered during rehabilitation in Butembo and to identify the trends of the five most common conditions during the study period. Method: Data were extracted from a rehabilitation programme connect to one centre in Butembo. A descriptive retrospective medical study was performed for the period between 2004 and 2007. Descriptive statistics with percentages were computed. The Chi-square test was used to evaluate the differences with a probability of 5%. Results: Cerebral palsy (46.9%), cataract (17.3%), clubfoot (11.8%), glaucoma (6.8%), and cleft lip (4.5%) were the most commonly encountered conditions, with cerebral palsy the most common condition throughout the study period. With regard to gender, male patients were significantly more affected by cataracts (p = 0.0290), clubfoot (p < 0.0100) and glaucoma (p < 0.0100) than female patients. Children aged five or younger had a higher incidence of cerebral palsy (χ2 = 263.2, df = 1, p = 0.0000) cataract (p = 0.0170), clubfoot (p < 0.0010), and glaucoma (p = 0.0010). Additionally, the overall comparisons by gender and age demonstrated differences for the five most common conditions (χ2 = 15.3, df = 4, and p = 0.0040; and χ2 = 114, df = 4, and p < 0.0001 for gender and age, respectively). Conclusion: Common conditions and associated factors were identified that will add to the effectiveness of the programme in terms of materials needed, staff skills, and programming. Special skills are still needed to help treat some acute conditions that can be handled at the rehabilitation centre, and a triage of attending rehabilitation centres could improve the effectiveness of the programme and lower the possibility of missed opportunities for acute stage patients.